PENGARUH EFEKTIVITAS PEMERIKSAAN PAJAK DAN EFEKTIVITAS PENAGIHAN PAJAK DENGAN SURAT PAKSA TERHADAP PENERIMAAN PAJAK PADA KANTOR PELAYANAN PAJAK PRATAMA BATAM UTARA - Lobinsen Lobinsen; Vargo Christian L. Tobing (JURNAL AKUNTANSI BARELANG, 2019)
The purpose of this study to determine the effectiveness of tax audits and effectiveness of tax collection by forced letter towards tax revenue. The object from the purpose of this study is tax service office batam north. The method used is quantitative descriptive. Data collection techniques in this study using boring sampling that sampling techinuque is retrieve all data from the existing population. In this study, the result of detailed examination that the effectiveness of tax audits is partially significant towards tax revenue, where the t count 17,429 > t table 2015 or with the significant level of t count 0,003 < 0,05. In this study, the result of detailed examination that the effectiveness of tax collection by forced letter also partially significant towards tax revenue, where the t count 11,404 > t table 2015 or with the significant level of t count 0,008 < 0,05. The result of The effectiveness of tax audits and effectiveness of tax collection by forced letter simultaneously towards tax revenue at tax service office batam north, where f count 387,645 > f table 5,786 with significant level of f count 0,003 <0,05.